A Parachute Suturing Technique for Rotator Cuff Tear - Zhenlong Liu, M.D.; Yajie Wang, M.D.; Ping Liu, M.D. (Arthroscopy Techniques)
Rotator cuff tear is a common type of injury. For the treatment of rotator cuff tears, arthroscopic surgery is widely used. However, for massive rotator cuff tears, the rate of recurrent tears after arthroscopic surgical repair is higher. This article describes an improved double-row suture technique combining vertical mattress suture and double-pulley techniques. This technique increases the strength and stability of the suture and reduces cutting damage to the tendon so as to reduce the risk of retear.